Effects of polymerization conditions on the properties of poly(furfuryl alcohol) composite membranes - He, L.; Li, D.; Dong, Dehua; Yao, J.; Huang, Y.; Wang, H. (John Wiley and Sons Inc, 2012)
Poly(furfuryl alcohol) (PFA) composite membranes were prepared by polymerization of furfuryl alcohol (FA) using sulfuric acid (H2SO4) as the catalyst and polysulfone ultrafiltration membrane as the substrate. The membrane samples were characterized by ATR-IR, TGA, SEM, and gas permeation technique. The effects of synthesis conditions including the FA/H2SO4 molar ratio, polymerization temperature, and the type of solvent on the chemical structure, surface morphology, and gas permeation properties of PFA composite membranes were studied. Our results showed that the suitable synthesis conditions for the preparation of PFA composite membranes with smooth surfaces and uniform structure include (1) FA/H2SO4 molar ratios: 74-300, (2) polymerization temperatures: 80–100°C, and (3) solvents: ethanol and acetone. The PFA composite membrane prepared with a FA/H2SO4 molar ratio of 250, a polymerization temperature of 80°C and ethanol as the solvent exhibited the highest H2/N2 ideal selectivity (xH2/N2 ), and a H2 permeability of 206 Barrers.